(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Mobile Ad-hoc network (MANET) is a collaboration of portable nodes as well as some computing devices which can be placed arbitrarily anywhere in the network to perform a particular task such as data transmission and message passing for various applications. The nodes can transmit data in a particular range and the nodes are capable of changing their location frequently. In previous research, the energy consumption is main issue and hence the overall routing performance is reduced significantly. To overcome the abovementioned issue, in this research, Particle Swarm Optimization-Adhoc On Demand Distance Vector (PSO-AODV) routing protocol is proposed. In this research, the Cluster Head (CH) is selected using PSO algorithm based on the best objective function values. The CH node has capability of rapid packet delivery ratio and better lower energy consumption. The PSO algorithm is used to select the optimal node and increases effective routing procedure. The routing process is done by using AODV protocol in this research. This is used to provide efficient path discovery and provides fast packet transmission and response. Thus the proposed PSO-AODV scheme provides superior performance rather than the existing approaches. The result concludes that the proposed PSO-AODV approach has lower energy consumption, lower end to end delay, higher packet delivery ratio and higher network lifetime than the existing approaches.